Application of a slit ceiling based on thermally activated building systems in a daylight‐harvesting office space with direct solar radiation. Issue 4 (20th September 2022) - Shindo, Kan; Shinoda, Jun; Ikai, Ken; Takenaka, Takeshi; Tamura, Shuichi; Kobori, Tetsuo; Tanabe, Shin‐ichi
Abstract: In recent years, an increasing number of offices have actively harvested daylight for the well‐being of occupants. However, if large windows are provided for daylight harvesting, the amount of solar heat gain increases, leading to poor energy efficiency and deteriorated indoor environment. Therefore, the objective of this study was to verify the radiant cooling effect of ceiling slits in an office building based on thermally activated building systems to achieve both daylight harvesting and solar removal through field measurements. In this study, the radiant cooling capacity of a slit ceiling and the indoor radiant environment were measured in a research facility in Fukui City, Japan, during spring (March 16–30) and summer (August 17–31) in 2020.